Analisis Pertanyaan Retorika dalam Ayub 40:1-28 - Kalis Stevanus (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2018)
Abstract. The purpose of the analysis of the rhetorical question in Job 40: 1-28 is to look at theological and practical implications. Theologically: 1) Everything under God's control. Including Job with all the agonizing suffering he experienced remained under God's control; 2) Keep believing in God even if you do not feel His physical presence; 3) Behind the suffering of the righteous man is the divine will of God. God never allows anything to happen to believers, without God's purpose in it. In suffering there is God's gracious will, in God's will, there is His grace. So believers can reach His great purpose and plan. Practically: 1) God is big, strong and we are small, weak. Let believers  keep giving thanks to God even in suffering, then pray (ask) to God for strengthening us when we face the tests of faith; 2) Live honestly and humbly. Do not despise or judge a person for not having the spiritual experience that Ayub once experienced. For the Lord opposes the proud and the pity of the humble; 3) Rely completely on God. In both temptation and suffering, there is nothing better that believers can do than always depend entirely on God.Abstrak. Tujuan analisis pertanyaan retorika dalam Ayub 40:1-28 ini adalah untuk melihat implikasi teologis dan praktis. Secara teologis: 1) Segala sesuatu di bawah penguasaan dan kendali Tuhan. Termasuk juga Ayub dengan segala penderitaan berat yang dialaminya tetap berada di bawah penguasaan dan kendali Tuhan; 2) Tetaplah percaya pada Tuhan walau tidak merasakan kehadiran-Nya secara fisik ; 3) Di balik penderitaan orang saleh terkandung kehendak Allah yang rahmani. Tuhan tidak pernah mengizinkan sesuatu menimpa orang percaya, tanpa maksud Tuhan di dalamnya. Di  dalam penderitaan ada kehendak Tuhan yang rahmani, di dalam kehendak Tuhan ada anugerah-Nya, sehingga orang percaya bisa mencapai maksud dan rencana-Nya yang agung. Secara praktis: 1) Tuhan itu besar, kuat dan manusia kecil, lemah. Hendaklah orang percaya tetap bersyukur kepada Tuhan sekalipun dalam penderitaan dan berdoalah (mintalah) kepada Tuhan agar Ia menguatkan saat-saat menghadapi ujian-ujian iman; 2) Hiduplah jujur dan rendah hati. Janganlah memandang rendah atau menghakimi seseorang karena tidak memiliki pengalaman rohani seperti yang dialaminya. Sebab Tuhan menentang orang sombong dan mengasihani orang yang rendah hati; 3) Bergantunglah sepenuhnya kepada Allah. Dalam pencobaan maupun penderitaan, tidak ada yang lebih baik yang dapat dilakukan orang percaya selain bergantung sepenuhnya kepada Allah.